The E.M.U. Presents the 9th Pacific Northwest Art Annual. (Eugene : University of Oregon)
Wong, Anna ; Shepard Levine ; Johanson, George ; Shull, James ; Darbow, Carole ; Jule, Walter ; Manarey, Thelma ; Givler, William ; Spilman, Craig ; Deweese, Robert ; Morgan, John ; Marcoux, Eric ; Bunse, Donald ; etc.
The E.M.U. Presents the 9th Pacific Northwest Art Annual, University of Oregon, Eugene, April 21 - May 16
boek